Controlled Drug Delivery in Metronidazole-Containing Bioactive Endodontic Cements. (2022) - De Souza Balbinot, G.; Leitune, V.C.B.; Zatta, K.C.; Benin, T.; Visioli, F.; Staniscauski Guterres, S.; Collares, F.M.
Abstract : Purpose/Aim: This study aims to formulate metronidazole liquid nanocapsules (MTZLNC) and evaluate their effect on the physical-mechanical and biological properties of calcium silicate-based bioactive endodontic cements. Materials and Methods: The MTZLNCs were formulated by deposition of preformed polymer and characterized by laser diffraction and high-performance liquid chromatography (HPLC). Calcium silicate (CS) particles were synthesized via the sol-gel route and mixed to 10 wt% CaWO4 as a radiopacificant. Cements were formulated by mixing the CS/CaWO4 powders with a liquid containing MTZLNC at two different concentrations: 0.3 mg/ml and 0.15 mg/ml. Cements were prepared with distilled water as the liquid was used as a control. The cements radiopacity, setting time and flow were evaluated following ISO 6876 recommendations. The compressive strength analysis was conducted according to ISO 9917. pH was evaluated after immersion in water, while mineral deposition on the surface of the sample was analyzed at up to 28-days immersions in SBF. Cell behavior was evaluated by the viability of cells by SRB and MTT, and the antibacterial activity against Enterococcus faecalis was analyzed immediately and after nine months of water storage. Results: MTZLNCs were successfully formulated with a 157 nm diameter and 83.44% encapsulated drug. The cements radiopacity was not affected by the presence of MTZLNCs and all groups reached the requirements of ISO 6876. An Increased flow was obtained with the two MTZLNCs concentrations, and all values were within the requirements of ISO 6876. The setting of cements was detected at 20 minutes for the control group and 18 minutes for 0.30 mg/ml concentration, without statistically significant difference between groups. Lower strength values were found when MTZLNCs were used. The incorporation of MTZLNCs maintained the ability of cements to increase pH media and promote mineral deposition over the samples. Pre-osteoblastic cell viability drops to around 80% with the 0.3 mg/ml concentration and at the same concentration, a reduction in E. faecalis CFU was observed both immediately and after nine months in water storage. Conclusions: The successful formulation of MTZLNCs allowed the development of antibacterial calcium silicate based-cements with suitable physicochemical properties and bioactivity. The 0.3 mg/ml concentration in cements liquid promoted effective and sustainable antibacterial activity.